Penerapan Arsitektur Islam pada Bangunan Masjid At-Thohir di Depok Jawa Barat - Carissa Ghefira; Pancawati Dewi; Lia Rosmala Schiffer (Jurnal Arsitektur Wastu Padma, 2024)
Architecture is born from a creative and innovative design that responds to functional needs and architectural values that want to be communicated to its users. Islamic architecture as a cultural work of Muslims is based on the values of Islamic teachings and culture. Through understanding and interpreting architectural works, the values of Islamic teachings and culture can be recognized. This research takes as its object the At-Thohir Mosque which is located on Jalan Mochamad Thohir RT 01 RW 12, Tapos - Depok West Java 16457, opposite the At Thohir plaza. This mosque was built in 2018 and inaugurated on March 9 2022 by President Joko Widodo. This research discusses the application of Islamic architectural themes and their meaning. The use of Islamic architecture as an element or support for a building has a meaning that represents the function and values of the architecture. This research uses descriptive qualitative methods and data collection techniques based on observation, interviews and literature study. The research results show that the application of architectural concepts can be found in the use of domes, towers, Middle Eastern architectural styles, elements, ornaments and the meanings of mosques as places of worship and houses of God.